Introducing the Visual Art through Concrete Poetry in the EFL Classroom: A Case Study - beloufa, chahra (International Journal of Language and Literary Studies, 2021)
Teaching poetry offers the teacher of literature some basic and active ways to engage students in learning English because of poetry’s rich language which represents an opportunity for learners to explore meanings and be able to formulate creative responses. One must be aware of the fact that poetry includes various types which differ in forms, and each one of these may have a particular influence on students? learning literature; that is why one centralized the research area on concrete poetry or what is called visual poetry too. This study aims to teach students not only to read and listen to a poem but to develop the skill of creativity through rewriting and this ability would be provoked by the visual shape of the concrete poem. One is trying to bring fun in the EFL classroom and particularly during the literature lecture where students are probably bored by analyzing every line and stanza. So, all these aims were to be concrete via a test, observation and questionnaire. These scientific tools confirmed one’s hypotheses about how positive is concrete poetry for the group of the third-year English L.M.D. students at the University of Djilali Liabes, Sidi Bel Abbes